Construction of copper (II) affinity- DTPA functionalized magnetic composite for efficient adsorption and specific separation of bovine hemoglobin from bovine serum. (1st October 2020) - Wang, Jundong; Guan, Huiyuan; Liang, Qionglin; Ding, Mingyu
Abstract: In this work, the copper (II) affinity-DTPA (Diethylene triamine pentacetate acid) functionalized magnetic composite was prepared and as an outstanding separation platform to isolate specific bovine hemoglobin (BHb) from bovine serum. Firstly, the Fe3 O4 microspheres were prepared via solvothermal method, followed by silanization with TEOS (Tetrathoxysilane) and coating with APTMS (3-Aminopropyl trimethoxysilane). Then incorporating the DTPA ligands via the amino/anhydride reaction. Finally, the target adsorbents (Fe3 O4 @SiO2 @NH2 @DTPA@Cu 2+ microspheres) were obtained via charging with copper ions. The resulting materials could selectively and specifically isolate BHb with a high maximum capture capacity of 911.3 mg g −1 . The absorbed BHb was easily eluted with a recovery of 82.4% by using 0.1 M of Na2 CO3 -Histidine as eluent. And the real sample analysis of Fe3 O4 @SiO2 @NH2 @DTPA@Cu 2+ microspheres was also tested using bovine serum, which was identified using MALDI-TOF Ms and SDS-PAGE analysis. The excellent results demonstrate that Fe3 O4 @SiO2 @NH2 @DTPA@Cu 2+ microspheres would be a good bioseparation material for biomacromolecules like histidine-tagged proteins. Graphical abstract: The copper (II) affinity-DTPA functionalized magnetic composite prepared by facile method were used as novel adsorbents for the selective separation of BHb. Image 1 Highlights: The copper (II) affinity-DTPA functionalized magnetic composite was prepared. The method possessed high selectivity, binding capacity and satisfying recovery. Specific separation of BHb from real biological sample was obtained.